Periodic cellular automata of period-2 - Ganikhodjaev, Nasir; Saburov, Mansoor; Asimoni, Raihan (Institute Mathematical Sciences, Universiti Putra Malaysia, 2016)
In this paper, we introduce a notion of periodic one-dimensional cellular automata of period-2 and study different properties of such kind of cellular automata. Moreover, we shall introduce an A− cellular automata which is not shift commuting of any power. We calculate entropy of some periodic cellular automata with period two and present simulation for some fractal type periodic cellular automata